Review of the subgenus Ainocarabus Mandl, 1973 of the Russian Far East (Coleoptera: Carabidae) - Obydov, Dmitry (Acta entomologica slovenica (Ljubljana), 2007)
The two species of the subgenus Ainocarabus Mandl, 1973 are studied. One new subspecies, Carabus (Ainocarabus) kolbei urupiensis ssp. n., is described. Status, type localities and areas of some taxa are specified. A key to all species and subspecies of the group and a distribution map are presented. Color photos of all taxa of the subgenus are added.
Keywords: entomologija; Hokkaido; hrošči; prevalence; razširjenost; Rusija; taksonomija